Confronting suburban school resegregation in California - Hurd, Clayton A. (Contemporary ethnography., 2014)
In this ethnographic study of the school district struggles in Central California, Clayton A. Hurd explores the core issues at stake in campaigns to reorganize districts into ethnically separated schools as well as the resistance against them mobilized by the working-class Latino community.